Properties of MSC populations enriched in CD146-expressing MSCs – a systematic review and meta-analysis of in vitro studies - Behm, Christian; Schwarz, Katharina; Miłek, Oliwia; Krämmer, Andreas; Andrukhov, Oleh (Frontiers in Bioengineering and Biotechnology, 2025)
IntroductionMesenchymal stromal cells (MSCs) are promising therapeutic candidates in regenerative medicine and the treatment of inflammatory diseases, yet their therapeutic effectiveness is limited by their heterogeneity. Clinical outcomes may be enhanced by isolating MSC subpopulations based on surface markers, including CD146. Many in vitro studies have investigated various cellular properties of MSC subpopulations that are enriched in CD146-expressing cells (CD146Enr.) compared to those that are depleted in CD146-expressing cells (CD146Depl.) and/or heterogeneous populations. Hence, this review aimed to systematically explore the basic cellular characteristics of MSC populations with different levels of CD146-expressing cells.MethodsTwo electronic databases were searched until 9 September 2024. Studies were screened using PICO-based eligibility criteria whilst following PRISMA guidelines. Risk of bias was assessed by evaluating reporting and methodological criteria, modified from Samuel et al. A Meta-analysis was performed on four studies on population doubling time (PDT) and five studies on colony-forming (CF) potential comparing CD146Enr. with CD146Depl. populations.ResultsA total of 29 in vitro studies were covered by this systematic review. PDT was slightly higher in CD146Enr. MSCs compared to CD146Depl. MSCs, but without statistical significance (2.52 hours, 95% CI -7.69, 12.74, p = 0.63, n = 19 donors). Contrary, CD146Enr. populations displayed significantly higher CF potential (1.29, 95% CI 0.41, 2.16, p = 0.004, n = 25 donors). All four studies assessing migration reported enhanced migratory potential in CD146Enr. populations. Results from tri-lineage differentiation, proliferation, and immunomodulation were highly variable across studies.ConclusionOverall, this systematic review indicates that CD146Enr. MSCs demonstrate only partially enhanced cellular characteristics, depending on the investigated study. The substantial heterogeneity across included studies limits firm conclusions. To enable robust comparisons and to fully evaluate the clinical potential of CD146Enr.MSCs, standardized experimental protocols and outcome measures are needed.